Familial periodontal disease in the cayo santiago rhesus macaques. Issue 1 (24th February 2015) - Gonzalez, Octavio A.; Orraca, Luis; Kensler, Terry B.; Gonzalez‐Martinez, Janis; Maldonado, Elizabeth; Ebersole, Jeffrey L.
Abstract : Substantial ongoing research continues to explore the contribution of genetics and environment to the onset, extent and severity of periodontal disease(s). Existing evidence supports that periodontal disease appears to have an increased prevalence in family units with a member having aggressive periodontitis. We have been using the nonhuman primate as a model of periodontal disease for over 25 years with these species demonstrating naturally occurring periodontal disease that increases with age. This report details our findings from evaluation of periodontal disease in skulls from 97 animals (5–31 years of age) derived from the skeletons of the rhesus monkeys ( Macaca mulatta ) on Cayo Santiago. Periodontal disease was evaluated by determining the distance from the base of the alveolar bone defect to the cemento‐enamel junction on 1st/2nd premolars and 1st/2nd molars from all four quadrants. The results demonstrated an increasing extent and severity of periodontitis with aging across the population of animals beyond only compensatory eruption. Importantly, irrespective of age, extensive heterogeneity in disease expression was observed among the animals. Linking these variations to multi‐generational matriarchal family units supported familial susceptibility of periodontitis. As the current generations of animals that are descendants from these matrilines are alive, studies can be conducted to explore an array of underlying factors that could account for susceptibility or resistance to periodontal disease. Am. J. Primatol. 78:143–151, 2016. © 2016 Wiley Periodicals, Inc.